Systematics of the caecilian family Chikilidae (Amphibia: Gymnophiona) with the description of three new species of Chikila from northeast India - Kamei, Rachunliu G.; Gower, David J.; Wilkinson, Mark; Biju, S. D. (Zootaxa, 2013)
A taxonomic review of the monogeneric northeast Indian caecilian family Chikilidae is presented based on 64 specimens. Chikila fulleri (Alcock, 1904), known previously only from a single specimen collected more than 100 years ago, is re-diagnosed and characterised based on recent collections. We describe three additional species new to science, Chikila al-cocki sp. nov., Chikila darlong sp. nov., and Chikila gaiduwani sp. nov. This species-level taxonomy is consistent with mitochondrial DNA sequence data. A key to the species of Chikila is presented.